16 GENETIC ANALYSIS IDENTIFIED NOVEL LOCI ASSOCIATED WITH IBD. (18th January 2018) - Li, Dalin; Haritunians, Talin; Potdar, Alka; McGovern, Dermot P B
Abstract: Introduction: More than 200 genetic loci have been identified in Inflammatory Bowel Disease (IBD). However, those loci do not explain the full hereditability of IBD, suggesting there are more genetics variants with weak or moderate effect sizes. To further expand our understanding of the biology of this complex disease, we screened for additional IBD loci in an independent cohort and replicated the findings in the IIBDGC cohort. Methods: 3, 312 IBD cases from Cedars-Sinai Medical Center and 5, 220 family and population-based controls with ImmunoChip data were included as the discovery cohort. Top SNPs were then replicated in the IIBDGC cohort (30179 cases and 29678 controls, having excluded all samples from the discovery stage). Inverse-variance Meta-Analysis was utilized to combine results from both cohorts. Results: In addition to the known IBD genes including IL23R, HLA and NOD2, we identified multiple novel genes associated with IBD. Those genes include: CCL21 (in CD, OR=0.88, p=2.93E-8) which is a CCR7-binding chemokine that plays a vital role by modulating the circulation of T cells and dendritic cells; SEC61B (in all IBD, OR=0.93, p=1.68E-8) which is essential for nuclear transport of epidermal growth factor receptor (EGFR); RRM1(in CD, OR=0.91, p=3.64E-8) which plays an important role in DNA synthesis and damage repair; ETS1 (in all IBD, OR=1.08, p=4.39E-9) which codes for a sequence-specific transcription factor whose expression plays an important role in the development of hematopoietic cells, particularly in T- and natural killer (NK) lineages. eQTL analyses indicates that top SNP (rs10835755) in RRM1 is a strong eQTL of RRM1 gene itself (In GTEx, p = 3.20E-20, 6.20E-14 and 3.4E-6 in artery, Esophagus and Colon, respectively). More functional analyses of the novel loci are underway. Conclusion: Novel loci identified in current study strongly suggest that larger sample sizes are warranted to further understand the genetic basis of IBD.